Ancillary services - The current situation in the Iberian electricity market and future possible developments - João Tomé Saraiva (2011)
This paper analyses and discusses the current situation in Portugal and in Spain regarding the procurement and the supply of the ancillary services considered in the Codes for the Operation of these two power systems. This is relevant because Portugal and Spain share a common day ahead and bilateral contract electricity market since 2007. However, several technical activities as the procurement and the provision of Ancillary Services are not yet entirely harmonized and fully integrated and continue to be provided within the control area of each country. Accordingly, this paper discusses three possible approaches that the two TSO's can adopt to further enlarge this integration. Then, tertiary reserve is taken as an example to illustrate the advantages that can be obtained if it is used a common list of bids from the two countries. The Case Study analyses four situations including the present mechanisms used to procure tertiary reserve, as well as the use of a common bid list admitting different values for the capacity of the interconnection lines between the two countries. Based on these results, the paper provides a discussion on the mentioned three integration models addressing their advantages and practical difficulties.